2020
DOI: 10.1371/journal.pone.0232019
|View full text |Cite|
|
Sign up to set email alerts
|

S-Nitrosylation of G protein-coupled receptor kinase 6 and Casein kinase 2 alpha modulates their kinase activity toward alpha-synuclein phosphorylation in an animal model of Parkinson’s disease

Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder which is mostly sporadic but familial-linked PD (FPD) cases have also been found. The first reported gene mutation that linked to PD is α-synuclein (α-syn). Studies have shown that mutations, increased expression or abnormal processing of α-syn can contribute to PD, but it is believed that multiple mechanisms are involved. One of the contributing factors is post-translational modification (PTM), such as phosphorylation of α-syn at serine 129 by G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Interestingly, the α-synuclein C-terminal tail contains the majority of phosphorylation sites ( Figure 3 ). Phosphorylation of α-synuclein Ser129 is mediated by several kinases such as G-protein-coupled receptor kinases (GRKs) [ 54 , 55 , 56 ], casein kinase II [ 56 , 57 , 58 ], polo-like kinases [ 59 , 60 , 61 ], and leucine-rich repeat kinase 2 (LRRK2) [ 62 , 63 ]. Below, we summarize the α-synuclein phosphorylation kinases and describe the associated pathogenic neurotoxicity.…”
Section: Kinases That Phosphorylate α-Synuclein and Their Association...mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the α-synuclein C-terminal tail contains the majority of phosphorylation sites ( Figure 3 ). Phosphorylation of α-synuclein Ser129 is mediated by several kinases such as G-protein-coupled receptor kinases (GRKs) [ 54 , 55 , 56 ], casein kinase II [ 56 , 57 , 58 ], polo-like kinases [ 59 , 60 , 61 ], and leucine-rich repeat kinase 2 (LRRK2) [ 62 , 63 ]. Below, we summarize the α-synuclein phosphorylation kinases and describe the associated pathogenic neurotoxicity.…”
Section: Kinases That Phosphorylate α-Synuclein and Their Association...mentioning
confidence: 99%
“…Wu et al reported that CK2α can be S-nitrosylated by nitric oxide (NO). Intriguingly, S-nitrosylation of CK2α enhanced the kinase activity of this catalytic subunit towards the phosphorylation of α-synuclein at Ser129 [ 56 ]. These data indicate that CK2α can enhance the phosphorylation of pSer129 α-synuclein.…”
Section: Kinases That Phosphorylate α-Synuclein and Their Association...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory GRK2 S-nitrosylation confirms the prior findings showing that NO/SNO can promote GPCR signaling [ 116 , 117 ] since GRK2 inhibition will prevent desensitization of receptors. GRK6 is also reported to be S-nitrosylated in an age-dependent manner resulting in enhanced kinase activity and this modification was suggested to contribute Parkinson’s disease [ 118 ] ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation of α-syn at S129 regulates physiological function and remarkably promotes their aggregation, critically participates in the pathogenesis of PD as an important molecular event. Casein kinase 2 (CK2) is the major one of the kinases that mediate α-syn phosphorylation at S129 ( Perez et al, 2011 ; Wu et al, 2020 ). It consists of two regulatory subunits β and two catalytic subunits α that mainly contribute to the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%